Entrepreneurial Traits and Firms Performance: Evidence from SMEs in Nigeria - Okoli, Nuel; Okoli, Ifeanyi (West Science Journal Economic and Entrepreneurship, 2024)
The purpose of this research is to determine the influence of entrepreneurial traits on firm’s performance in selected small and medium enterprises (SMEs) in Anambra State, Nigeria. The research was supported by trait theory of entrepreneurship. The research employed survey research design. The population target consists of 548 registered small and medium-scale enterprises located in Awka South L.G.A, Anambra State. The study used sample of 240 respondents drawn from the registered small and medium-scale enterprises. Stratified random sampling was employed in identifying respondents. A structured questionnaire was incorporated in data collection. Face and content validity was adopted in the study. Cronbach alpha coefficient was useful in examining the research instrument. Cronbach alpha coefficient of 0.7 was used for reliability. The assembled data was examined by means of descriptive statistics and inferential statistics assisted by Statistical Package for Social Sciences (SPSS). Data presentation entailed usage of tables and percentages. The findings indicated that entrepreneurial traits had a positive significance influence on the performance of SMEs. The research concluded, risk taking propensity, innovativeness and resilience influence performance of SMEs in Anambra State Nigeria having been statistically significant and therefore considered. The study recommended that prospective entrepreneurs should be mindful of these factors and take advantage of them in their quest to improve their firm’s performance and competitiveness.